The take-off of the Saudi professional football league in the context of the 2030 vision: effect on the competitive balance - Bataineh, Mohammed Jamal; Guevara-Pérez, Juan Carlos; Martín-Vallespín, Emilio; Urdaneta-Camacho, Rudemarlyn (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examines the impact of Saudi Arabia's Vision 2030 on the competitive balance of the Saudi Professional League (SPL), focusing on how the entry of public investment funds (PIF) into club ownership has transformed the league's structure.MethodsCompetitive balance is measured using the Herfindahl Index of Competitive Balance (HICB), which captures the degree of concentration in the distribution of league points across ten seasons (2014/15–2023/24).ResultsResults indicate that the SPL's growth has been accompanied by greater imbalance between clubs, reducing competitive uncertainty and, potentially, spectator appeal. The main issue is not the inflow of capital or foreign players per se, but their concentration in a small number of teams.DiscussionDespite the deterioration in competitive balance, driven by widening financial disparities between a small group of clubs and the rest, the SPL has significantly increased its international visibility. This pattern appears consistent with the priorities of Vision 2030 to enhance the national brand image and soft power, although it may delay progress towards financial sustainability at the league level. At the same time, football can amplify the visibility and agency of local communities by creating spaces for participation and inclusion, suggesting that targeted grassroots initiatives could help translate international profile into durable domestic support. While debates about “sportswashing” persist, the broader policy intent of Vision 2030 aligns with the UN's 2030 Agenda emphasis on diversification. Ultimately, any durable impact should be assessed against measurable future social and economic outcomes.